Bidens sulphurea (Sch. Bip.): efeitos fotodinâmico e antibiótico dos extratos etanólicos de suas flores - Araújo Neto, Alexandre Dias de (2011)
This work had the aim to assess some biological eects of the Bidens sulphurea (Asterace ) (also know as Cosmos sulphureus), assessed eects were: cytotoxicity, antibiotic and phototoxicity. The phototoxicity was ephasized, since the primary aim of this work was to evaluate if this plant\'s pigments could be used as photosensitizers in the photodynamic therapy, in a non invasive way, using light emitted by LED, for treatment of dermatosis, particularly, onicomicosis. The conclusion of this work is that, of the two Bidens sulphurea varieties studied, the one that bear the greater photodynamic activity, when irradiated with white light, or red light ( 600 nm) and did showed greater antibiotic eect (in the dark) was the orange variety. The orange variety did showed an increase in the toxicidy to the Artemia salina nauplii, when irradiated with red light.